2019
DOI: 10.1016/j.neuroimage.2018.06.069
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific gray and white matter DTI atlas for human brain at 33, 36 and 39 postmenstrual weeks

Abstract: During the 3rd trimester, dramatic structural changes take place in the human brain, underlying the neural circuit formation. The survival rate of premature infants has increased significantly in recent years. The large morphological differences of the preterm brain at 33 or 36 postmenstrual weeks (PMW) from the brain at 40PMW (full term) make it necessary to establish age-specific atlases for preterm brains. In this study, with high quality (1.5 × 1.5 × 1.6 mm imaging resolution) diffusion tensor imaging (DTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 77 publications
(76 reference statements)
6
56
0
Order By: Relevance
“…These dMRI studies have demonstrated, for example, that limbic WM fibers appear earlier while the association WM fibers constituting major cortico-cortical connectivity appear later. By the start of the 3 rd trimester, except arcuate fasciculus, all major WM fibers can be identified with dMRI (Feng et al, 2016). The asynchronous and heterogeneous maturation of WM across regions in the 3 rd trimester has also been suggested by other neuroimaging studies (e.g.…”
Section: Introductionsupporting
confidence: 52%
“…These dMRI studies have demonstrated, for example, that limbic WM fibers appear earlier while the association WM fibers constituting major cortico-cortical connectivity appear later. By the start of the 3 rd trimester, except arcuate fasciculus, all major WM fibers can be identified with dMRI (Feng et al, 2016). The asynchronous and heterogeneous maturation of WM across regions in the 3 rd trimester has also been suggested by other neuroimaging studies (e.g.…”
Section: Introductionsupporting
confidence: 52%
“…Consistent with histological atlases (Bayer and Altman 2004), these dMRI findings have demonstrated that limbic WM fibers appear earlier while the association WM fibers constituting major cortico-cortical connectivity appear later. By the start of the 3 rd trimester, except the arcuate fasciculus, all other major WM fibers can be identified with dMRI (Feng et al, 2016). Asynchronous and heterogeneous maturation of WM across regions in the 3rd trimester has also been suggested by other neuroimaging studies (e.g.…”
Section: Introductionmentioning
confidence: 58%
“…Considering there are equivalent JHU atlases available for younger third trimester time points (Feng et al, ) and older time points (Mori et al, ; Oishi et al, ), our neonatal WM atlas also has the benefit of facilitating longitudinal analyses of neuroimaging metrics from equivalent WM regions. Together with the large range of complementary multi‐parametric neuroimaging tools and techniques available, the combined M‐CRIB and M‐CRIB‐WM atlases will enable detailed structural and microstructural measures to be obtained in an accurate and age‐specific way for major cortical and subcortical regions of the neonatal brain, and now additionally for all major WM tracts and regions.…”
Section: Discussionmentioning
confidence: 99%
“…During the neonatal period, MRI images have relatively low spatial resolution due to small brain size and have different tissue contrast compared with older children and adults due to partial myelination and dynamic tissue properties in neonates (Heemskerk et al, ). Over the last decade, increasing efforts in the neonatal brain imaging field have led to development of several neonatal parcellated atlases (Alexander et al, ; Alexander et al, ; Blesa et al, ; de Macedo Rodrigues et al, ; Feng et al, ; Gousias et al, ; Kuklisova‐Murgasova et al, ; Makropoulos et al, ; Oishi et al, ; Shi et al, ; Shi et al, ). These atlases differ in image modality and quality, parcellation technique, and parcellation schemes.…”
Section: Introductionmentioning
confidence: 99%